2016
DOI: 10.1039/c6ra22430j
|View full text |Cite
|
Sign up to set email alerts
|

Constructing densely functionalized Hajos–Parrish-type ketones with six contiguous stereogenic centers and two quaternary carbons in a formal [2 + 2 + 2] cycloaddition cascade

Abstract: Efficient construction of Hajos–Parrish-type ketones with six contiguous stereogenic centers in a formal [2 + 2 + 2] cycloaddition cascade. The spontaneous resolution of racemic product without the need for chiral agent has been achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…The SDE refers to the spontaneous fractionation of nonracemic material into enantioenriched and depleted fractions when any physicochemical process is applied under totally achiral conditions [17][18][19]. The purification or separation of nonracemic sample by fractional crystallization and sublimation based on the SDE principle can be recalled from very early times, and is still of interest for many researchers [20][21][22][23]. Additionally, since the seminal works of P. A. Crooks [24] and E. Gil-Av [25], the SDE on different types of achiral chromatography including routine, gravity-driven column chromatography, medium pressure liquid chromatography (MPLC), high-performance liquid chromatography (HPLC) and gas chromatography (GC) has been intensively studied [26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…The SDE refers to the spontaneous fractionation of nonracemic material into enantioenriched and depleted fractions when any physicochemical process is applied under totally achiral conditions [17][18][19]. The purification or separation of nonracemic sample by fractional crystallization and sublimation based on the SDE principle can be recalled from very early times, and is still of interest for many researchers [20][21][22][23]. Additionally, since the seminal works of P. A. Crooks [24] and E. Gil-Av [25], the SDE on different types of achiral chromatography including routine, gravity-driven column chromatography, medium pressure liquid chromatography (MPLC), high-performance liquid chromatography (HPLC) and gas chromatography (GC) has been intensively studied [26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…As a continuation of our interest in domino organocatalysis reactions and in the course of subsequent study of the cascade Michael reactions (Scheme a,b), we observed a small amount of an unknown product in the reaction of 2-methylcyclopentane-1,3-dione and nitrostyrene with some organocatalysts. In particular, the unknown products increased in quantity when a cinchona primary amine (Q-NH 2 ) was applied as the catalyst (Scheme c).…”
mentioning
confidence: 99%
“…[17] Organocatalysts [18] have been successfully employed in the synthesis of steroids.T he proline-mediated intramolecular aldol reaction, reported in 1971, [19] is alandmark discovery in organocatalysis.This approach is effective for the synthesis of the Wieland-Miescher ketone,akey intermediate of the steroid synthesis. [20] Recently,Hong and co-workers reported the one-pot synthesis of as teroid system through organocatalyst-mediated Michael/Michael/aldol/Henry and Michael/ Michael/Henry reactions, [21] whereas Jørgensen and co-workers reported the construction of the steroid structure by using Torgovsd iene via ad ienamine intermediate. [22] List and coworkers reported as hort synthesis of estrone through chiral disulfonimide-mediated Torgov cyclization as ak ey step.…”
mentioning
confidence: 99%